Identifikasi Kondisi Atmosfer Kejadian Hujan Lebat Jakarta Selatan Berbasis Data Observasi, Satelit, dan Model ERA-5 (Studi Kasus 11 November 2024) - Oktabrian, Krisna Dwi; Darmawan, Yahya; Rahma, Nuzula Elfa; Franchitika, Rizky (Newton-Maxwell Journal of Physics, 2025)
On November 11, 2024, a heavy rainfall event with a recorded precipitation of 94.6 mm occurred in South Jakarta, leading to flooding in the area. This study aims to analyze the atmospheric factors that contributed to the event and emphasize the importance of integrating satellite data, numerical models, and observational data in understanding extreme weather phenomena. The data used in this study include ERA-5 reanalysis data from ECMWF, satellite imagery from Himawari-9, and observations from automatic rain gauges (ARG). The analysis results indicate that the heavy rainfall was influenced by several key factors, including significant moisture transport from the Indian Ocean, strong low-level convergence, and unstable atmospheric conditions. The convective available potential energy (CAPE) value approached 900 J/kg, and the relative humidity reached 90%, both supporting the development of deep convective clouds. These findings highlight the importance of integrating data from various sources in diagnosing and understanding the mechanisms behind extreme rainfall events in tropical urban regions.